PENERAPAN ASESMEN SUMATIF PADA MATA PELAJARAN IPAS DALAM KURIKULUM MERDEKA DI SDS TARBIYATUL ISLAM SAMBAS - Rona Rona (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The application of summative assessment is to measure whether or not the specified learning objectives have been achieved. The implementation of this summative assessment is carried out at the end of the semester to determine whether or not to pass. However, the implementation of summative assessment at SDS Tarbiyatul Islam Sambas is very contrary to the assessment criteria of the Merdeka curriculum, where the criteria for end-of-semester assessment in the Merdeka curriculum are that no students are not promoted, even though their PTS and PAS scores have not met the criteria. This summative assessment is carried out using test techniques. The technical test used is granular questions in the form of multiple choice and description. This study aims to analyze the application of summative assessment used in IPAS learning at SDS Tarbiyatul Islam Sambas. The research method used was descriptive qualitative research. Descriptive data collection obtained from observation, interview and documentation data collection. The subjects in this study were IPAS teachers at SDS Tarbiyatul Islam Sambas as research subjects and documentation as support. Data collection techniques are observation, interview, and documentation. To find out the results of the study, it is necessary to describe the results of interview research on IPAS teachers at SDS Tarbiyatul Islam Sambas in summative assessment in IPAS learning. The results of the research on the implementation of summative assessment in IPAS learning at SDS Tarbiyatul Islam are quite effective.